2006
DOI: 10.2224/sbp.2006.34.10.1297
|View full text |Cite
|
Sign up to set email alerts
|

Youth and Parental Perceptions of Parental Monitoring and Parent-Adolescent Communication, Youth Depression, and Youth Risk Behaviors

Abstract: Data from 752 Bahamian youth and their parents were analyzed to examine the relationship of youth depression with youth risk involvement, parental monitoring, and parent-youth communication. Depressed youth were older, more likely to engage in risk behaviors, and they perceived significantly lower levels of parental monitoring and higher levels of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
61
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(73 citation statements)
references
References 32 publications
11
61
0
1
Order By: Relevance
“…The results of their systematic review found that parental monitoring, parent-child interaction, and child disclosure led to delayed alcohol initiation as well as reduced levels of later drinking [68]. Additional support for the findings of the current systematic review were found in the results of other studies which show that parental monitoring significantly decreases adolescent risk behaviour such as sexual risk behaviours and decreased substance use [26,56,60,67]. Furthermore, parental communication has been found to Unclear.…”
Section: Discussionsupporting
confidence: 76%
“…The results of their systematic review found that parental monitoring, parent-child interaction, and child disclosure led to delayed alcohol initiation as well as reduced levels of later drinking [68]. Additional support for the findings of the current systematic review were found in the results of other studies which show that parental monitoring significantly decreases adolescent risk behaviour such as sexual risk behaviours and decreased substance use [26,56,60,67]. Furthermore, parental communication has been found to Unclear.…”
Section: Discussionsupporting
confidence: 76%
“…Conversely, adolescent children had higher scores on issues of conflict within the family. These findings, consistent with other studies may reflect parents' investment in portraying the family ecology in a more positive manner than their children [1,7]. Even though runaway youths consistently report numerous chronic personal and family difficulties that precipitated their running away from parental homes, parents may feel family dynamics improve once the adolescent departs [5].…”
Section: Discussionsupporting
confidence: 87%
“…Research exploring parent and adolescent relationships in normative and clinical populations suggests that family members often have divergent perspectives [1]. Parents who have invested time and energy in maintaining integrated family relationships are more likely to report fewer family difficulties, whereas adolescents striving for independence and increased separation from parents are more apt to have unenthusiastic opinions of family life and relationships [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…These normative changes might account for the finding that during early adolescence, adolescents tend to view the family in relatively negative ways in comparison to their parents (e.g., Ohannessian and De Los Reyes 2014;Ohannessian et al 2000). In fact, relative to parents' reports, adolescents report lower levels of family satisfaction and family cohesion (Ohannessian et al 2000(Ohannessian et al , 1995, as well as higher levels of communication problems (De Los Reyes et al 2016b;Laird and De Los Reyes 2013;Reynolds et al 2011;Yu et al 2006). Consequently, increased divergence between adolescents' and parents' reports may relate to an increased mastering of adolescent normative developmental tasks.…”
Section: Converging Operations: When Adolescents' and Parents' Reportmentioning
confidence: 99%